Australia's experience with economic reform - Laura Berger-Thomson; John Breusch; Louise Lilley (The Australian Government, The Treasury, 2018)
This paper has been prepared to inform an officials level workshop at the IMF and World Bank Annual Meetings in Bali, Indonesia in October 2018. The paper will be discussed by Ms Laura Berger‑Thomson and a panel including Dr Changyong Rhee, Mr Charles Abel, Dr Mohamad Chatib Basri, Mr Rodrigo Valdés and Mr Nigel Ray. This paper discusses the factors and circumstances that influenced the course of the Australian economy over the past 40 years. It will discuss challenges Australia faced and events that motivated reform emphasising aspects unique to Australia as a commodity exporting country, geographically remote with a relatively small population.
Keywords: 330